Effect of intravenous lipid therapy in critically ill pediatric patients with calcium channel blocker toxicity - Sinan Yavuz; Ali Avcı; Rabia Gündoğan Serin; Mustafa Mesut Kaya; Dilfuza Ağalıoğlu (The Turkish Journal of Pediatrics)
Background. Overdose with calcium-channel blockers (CCBs) still maintain their importance with a high lethality rate after exposure. We report the intravenous lipid emulsion therapy (ILE) therapy in our CCB overdose patients.